Photography Service Booking System - Hans Putra Adhi; Tinuk (PT FORMOSA CENDEKIA GLOBAL, 2023)
Development of booking information system is a computer technology development that will help and ease human works. This research is focused at the Aditya Production photo studio owned by researcher’s friend. Aditya Production is in need of a system that can help advertising and communicating with customer. Researcher hoping that this system could help Aditya Production to advertise their photography services and ease customer’s access to gain help from professional photo studio. Designing the booking system starts with making program design using activity diagram, administrator and customer navigation system. This system’s made using Google Web Design. Waterfall Research and descriptive method are used in this research